Hubungan pendidikan ayah dan pendidikan ibu dengan kenakalan remaja pada remaja SMK X rangkasbitung tahun 2017 - Rita Ariesta (Akademi Kebidanan La Tansa Mashiro, 2017)
The study aims at investigating the relationship between father’s and mother’s education with juvenile delinquency. The design of the study was cross sectional, this research was conducted at Vocational School X Rangkasbitung. The number of population in this research are 85 people. The data are collected primarily using checklists and questionnaire instruments. The results of the bivariate test on father’s education education toward juvenile delinquency presents P value which means that, statistically, there is a relationship between father’s education and juvenile delinquency incidence = 0.002 (p 0.05) so that HO is rejected. The results of the bivariate test on mother’s education variable toward juvenile delinquency shows P = 0.008 (p 0.05) which indicates that there is a statistically significant relationship between mother’s education and juvenile delinquency. At the age of adolescence, teenagers need a figure who can be the motivaor and facilitator in this period. Parental involvement in this case can be a bridge for teenagers to help them solve the turmoil of adolescence, hence, it is important for parents to continue learning during the process of being a parent.